Pengaruh Perputaran Kas, Perputaran Persediaan, dan Perputaran Piutang Terhadap Profitabilitas - Kurniawan, Fahmi; Tri Bodroastuti; Wenny Ana Adnanti (Jurnal Ilmiah Aset, 2025)
This study aims to determine the effect of cash turnover, inventory turnover, and revenue turnover on profitability. The population in this study were pharmaceutical companies listed on the Indonesia Stock Exchange in 2019-2023. The sampling method used in this study was the purposive sampling method and a sample of 11 companies was obtained. The data used in this study were obtained from the annual financial report data of pharmaceutical companies listed on the Indonesia Stock Exchange in 2019-2023. The data analysis method in this study was multiple linear regression analysis. The results showed that partially, cash turnover had a significant negative effect on profitability and inventory turnover had a positive and significant effect on profitability, while receivables turnover had no effect on profitability.